Social Support and Job Stress: Moderation Role of Locus of Control - Karimi, Roohangiz; Alipour, Farhad (Journal of Asian Scientific Research, 2011)
The purpose of this study is to investigate theoretically how locus of control can moderate the relationship between social support and job stress so as to increase the effect of social support to reduce stress in the workplaces. By utilizing the proposed model the researchers explore how supervisors can increase locus of control among their employees in order to increase the effect of social support to decrease stress in the organizations. This study may help managers and human resource development practitioners to reduce job stress by better understanding the moderating role of locus of control in the relationship between social support and job stress based on the proposed model.